2001
DOI: 10.1103/physrevb.64.045405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intersubband scattering on weak localization in two-dimensional systems

Abstract: The theory of weak localization is generalized for multilevel 2D systems taking into account intersubband scattering. It is shown that weak intersubband scattering which is negligible in a classical transport, affects strongly the weaklocalization correction to conductivity. The anomalous magnetoresistance is calculated in the whole range of classically low magnetic fields. This correction to conductivity is shown to depend strongly on the ratios of occupied level concentrations. It is demonstrated that at rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…where the terms ∆σ (a) and ∆σ (b) correspond to the standard diagrams, which have been considered in detail in Refs. [17,19,20]. We neglect both valley and spinorbit splitting in Si MOS structures.…”
Section: Theorymentioning
confidence: 99%
“…where the terms ∆σ (a) and ∆σ (b) correspond to the standard diagrams, which have been considered in detail in Refs. [17,19,20]. We neglect both valley and spinorbit splitting in Si MOS structures.…”
Section: Theorymentioning
confidence: 99%
“…WL in a two-dimensional system with two occupied subbands has been theoretically studied [14,15]. It was shown that if short-range scattering is dominant and intersubband scattering is strong, the subbands couple and the electrons behave as if they occupy a single subband characterized by an average kinetic parameter.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that a crucial factor is a scattering between different types of charge carriers. Indeed, as it was shown for multiband compounds [22], multivalley systems [23,24], and topological insulators [25], if we take into account the scattering between different types of the quasi-particles, a multicomponent system effectively reduces to a single-component one from the view point of the weak localization/antilocalization.…”
mentioning
confidence: 89%